Antecedents of ERP systems implementation success: a study on Jordanian healthcare sector. Issue 4 (11th July 2016) - Almajali, Dmaithan Abdelkarim; Masa'deh, Ra'ed; Tarhini, Ali
Abstract : Purpose: – Most small- and medium-sized enterprises (SMEs) use some business management software to manage their daily operations. Ultimately they consider transitioning to an enterprise resources planning (ERP) system. However, implementing ERP system successfully is costly and complex, and often shows high disappointment rates or even abandonment due to need of fit with the business or social culture. In Jordan, large businesses have been using the ERP system for a long time, but SMEs usage of the system is relatively new. The purpose of this paper is to study the effect of ERP implementation success antecedents which consists of training, supportive leadership and ease of use on ERP implementation success itself through a mediating effect of user satisfaction. Design/methodology/approach: – Empirical data were collected using a survey questionnaire which was distributed to ERP users in Jordanian healthcare organizations. A total of 175 responses were collected and analyzed using structure equation modeling. Findings: – A significant relationship was found between these antecedents and ERP implementation success. Furthermore, user satisfaction plays a significant mediating role between ease of use and ERP implementation success. Practical implications: – The outcomes of this study are useful to ERP users as they would be able to strategize future ERP system implementation in different sectors such as education, manufacturing and insurance industry. Finally, the findings may be useful to ERP system adopters in different developing countries. Originality/value: – This is one of the first studies which adequately covers the relationships between antecedents of user satisfaction and ERP implementation success which consists of training, supportive leadership and ease of use on ERP implementation success itself through a mediating effect of user satisfaction.